The Association of Food Insecurity and Chronic Diarrhea on the Prevalence of Stunting in Children under 2-5 Years of Age - Marisa, Agnia; Hastuti, Vivilia Niken; Resti, Nina; Hardaningsih, Galuh; Ardiaria, Martha; Sugianto, Denny Nugroho; Afifah, Diana Nur (Journal of Sustainability Perspectives, 2025)
Stunting is associated with food insecurity and diarrheal infections. Age under five years is a golden age, which is very important for optimizing growth and development in the future. This study aimed to investigate the association between food insecurity and diarrhea and the prevalence of stunting in toddlers aged 2-5 years. Analytical observations using cross-sectional design. The study sample comprised 140 children aged 2-5 years. The sample was selected by simple random sampling. Data analysis was performed using univariate, chi-squared, Kruskal-Wallis, and multivariate tests. A total of 18.6% of the toddlers were stunted, 66 families were food insecure, and 31 toddlers had diarrhea. There was a relationship between chronic diarrhea and short nutritional status (p<0.001), and there was a significant relationship between food insecurity and the incidence of stunting (p=0.001). Results of the multivariate analysis using logistic regression. The final modal formula was log p (stunting) = -2.549 + 1.808 (parental income < minimum wage) + 6.098 (history of diarrhea) + 1.396 (food insecurity). Diarrhea is the dominant factor that most influences the incidence of stunting.